Formation of a protestant heritage intangible in Fortaleza, Ceará - Silva, Luiz Raphael Teixeira da (Geosaberes; Vol 8 No 16 (2017): Sept - DecDO - 10.26895/geosaberes.v8i16.585, 2017)
The research analyzes protestant ritual practices, with the purpose of recording the formation of an immaterial evangelical heritage in Fortaleza, capital of Ceará, located in the Brazilian Northeast. The analysis follows a cultural approach based on humanistic geography taking into account the culture in the understanding of the landscape. This landscape is analyzed beyond materiality, to understand the dimensions of patrimonialization through a methodology that values the intentions of the subjects, having data collected from participant observation. These data have been interpreted according to the relevance of the ideas, allowing final considerations that reflect on the elitist character that limits cultural practices to the molds that control social groups and restrict the human creative capacity in the name of the notorious cultural patrimony.
Keywords: Patrimônio, Evangélico, Paisagem